WOMEN, HAPPINESS, AND EDUCATION: AN ANALYSIS OF INDONESIAN FAMILY LIFE SURVEY (IFLS) DATA - Sa'diah, Halimatus; Aritonang, Gema Juita; Gusbet, Rani Attiqah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Happiness is important and desired by everyone, including adult women. Adult women have both domestic and public roles, making them vulnerable to depression or other mental disorders. There are many sources and components that can increase the happiness of adult women, one of which is the level of education. This study aims to provide an overview of the happiness of adult women in terms of their level of education, presenting a valid source of data to improve the happiness of Indonesian women. This study used secondary data from the Indonesian Family Life Survey (IFLS), with 7047 women aged 25-40 years as research subjects, and conducted regression analysis. The results showed that education level is significant in influencing the happiness level of Indonesian women (R2 = 0.012, F (1,6842) = 82.16, p < 0.001). The higher the education level of Indonesian women, the happier they would be. This study also examined age, marital status, and place of residence (rural or urban) for women's happiness.